Peran perpustakaan dalam meningkatkan literasi informasi di kalangan masyarakat: sebuah systematic literature review - Ningsih, Leila Setia; Sayekti, Retno (Pustaka Karya : Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2023)
Information literacy is a set of skills that everyone needs in finding information. The existence of information literacy encourages a person to be able to think more critically and be able to add new knowledge related to new concepts in the world of education. Information literacy skills are needed in today's digital era. The goal is to be able to filter all information received in order to avoid false information. Therefore this study aims to find out how the development of research regarding the role of libraries in increasing information literacy indexed by Sinta in the last 5 years, answer research questions that have been compiled and provide recommendations for further research. This study uses the Systematic Literature Review (SLR) method and uses the PRISMA (Preferred Reporting items for Systematic Review and Meta-analysis) protocol in the research phase. The literature search uses the publish or perish tool on the crossreff and google scholar databases in the 2018-2022 period. Thus, 13 journal articles were obtained that had passed the screening stage and had been assessed for quality using the CRAAP test (Currency, Reverence, Authority, Accuracy, and Purpose). The results of the study found that all articles were of good quality and each article had a different research design, program, program success indicators and research context. However, the results of the study also show that there is the same research objective in each literature, namely increasing the literacy movement in the community.